Effects of hardeners and amine compounds on formaldehyde emission from rubberwood/urea formaldehyde particleboard - Abd Ghani, Muhammad Aizat (2019)
Urea formaldehyde (UF) bonded-particleboard is one of building materials that contribute to the emittance of formaldehyde in enclosed area. Formaldehyde is classified as a type of carcinogen that can cause health problems. Numerous studies have been conducted to reduce formaldehyde emission from particleboard to meet the standard requirement. However, attempts to lower down the formaldehyde emission are always accompany with the reduction of the board performance. In this study, methods to reduce formaldehyde emission while maintaining it or at least lowering the reduction of properties of UF-bonded particleboard were developed through either incorporating amine compounds in the resin system or through post treatment on the surface of particleboard. Amine compounds act as formaldehyde scavenger, meanwhile and ammonium or aluminium-based compound were used as hardeners to speed up the curing of the resin. Homogenous rubberwood particleboards with nominal dimension of 340 mm by 340 mm by 12 mm (thick) with target density of 650 kg/m3 were produced using the formulated resin system. A preliminary study was first conducted to determine the physical properties of UF adhesive admixed with ammonium or aluminium-based hardeners. The pH and gelation time of this adhesive were found to be lower, but the viscosity was higher compared to the values found in the true UF resin. Adhesive with aluminium-based hardener had lower pH and gelation time with significantly higher viscosity than the adhesive with ammonium-based hardener. The addition of the hardeners was also found to reduce the free formaldehyde content in the adhesive. Particleboard bonded with these adhesives were also found to have low formaldehyde emission. In the second phase of the study, amine compounds, methylamine, ethylamine and propylamine (0.5 to 1% w/v based on solid UF resin) were incorporated in the adhesive mixture. It was found that UF adhesive with the presence of amines possessed higher thermal stability, compared to that without amines. Boards fabricated using these resin systems had very low formaldehyde emission. To further improve the performance of the boards, the pressing time was increased from 270 s to 390 s and UF resin concentration was increased from 8 to 12% and, the results revealed that the reduction of formaldehyde improved significantly with the performance of the board successfully met the standard requirement. Post-treatment of particleboard using amine compounds fabricated with 8% UF resin content and were hot-pressed for 270 seconds at 180 C also was carried out to compare the effect with the previous (add-in) method. The compounds were spread on the surface of the fabricated particleboard with a spread rate of 40 g/m2 to 60 g/m2 and show a substantial reduction in formaldehyde emission value from the board. Generally, post treatment application results showed that the formaldehyde emission was successfully reduced without significantly affecting other properties of the particleboard compare to add-in application with the same processing parameters.